Enzymatic Transesterification of Kraft Lignin with Long Acyl Chains in Ionic Liquids - Lise Hulin; Eric Husson; Jean-Pierre Bonnet; Tatjana Stevanovic; Catherine Sarazin (Molecules, 2015)
Valorization of lignin is essential for the economic viability of the biorefinery concept. For example, the enhancement of lignin hydrophobicity by chemical esterification is known to improve its miscibility in apolar polyolefin matrices, thereby helping the production of bio-based composites. To this end and due to its many reactive hydroxyl groups, lignin is a challenging macromolecular substrate for biocatalyzed esterification in non-conventional media. The present work describes for the first time the lipase-catalyzed transesterification of Kraft lignin in ionic liquids (ILs). Three lipases, three 1-butyl-3-methylimidazolium based ILs and ethyl oleate as long chain acyl donor were selected. Best results were obtained with a hydrophilic/hydrophobic binary IL system (1-butyl-3-methylimidazolium trifluoromethanesulfonate/1-butyl-3-methylimidazolium hexafluoro- phosphate, 1/1 v/v) and the immobilized lipase B from Candida antarctica (CALB) that afforded a promising transesterification yield (ca. 30%). Similar performances were achieved by using 1-butyl-3-methylimidazolium hexafluorophosphate as a coating agent for CALB rather than as a co-solvent in 1-butyl-3-methylimidazolium trifluoromethane-sulfonate thus limiting the use of hydrophobic IL. Structural characterization of lignin oleate was performed by spectroscopic studies (FTIR and 1H-NMR). The synthesized lignin oleate exhibited interesting thermal and textural properties, different from those of the original Kraft lignin.